2019
DOI: 10.3390/ijms20184598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Central Injection of Neostigmine on the Bacterial Endotoxin Induced Suppression of GnRH/LH Secretion in Ewes during the Follicular Phase of the Estrous Cycle

Abstract: Induced by a bacterial infection, an immune/inflammatory challenge is a potent negative regulator of the reproduction process in females. The reduction of the synthesis of pro-inflammatory cytokine is considered as an effective strategy in the treatment of inflammatory induced neuroendocrine disorders. Therefore, the effect of direct administration of acetylcholinesterase inhibitor—neostigmine—into the third ventricle of the brain on the gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH) secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The ex vivo experiment conducted on the AP derived from sheep showed that LPS addition into a medium with explants collected from animals already treated with LPS significantly increased IL6 expression, which was not stated for explants derived from animals not treated with LPS [93]. Intracerebroventricular (icv) administration of LPS into the third ventricle increased the expression of IL6 in the ovine hypothalamic preoptic area during the reproductive season [94]. Further, IL1β injection into the third ventricular of the ovine brain caused a significant increase in IL6 and IL6ST expression in both photoperiods, while IL6R expression increased only during the short-day period at the level of the pineal gland [95].…”
Section: The Influence Of Leptin On Proinflammatory Cytokines During Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ex vivo experiment conducted on the AP derived from sheep showed that LPS addition into a medium with explants collected from animals already treated with LPS significantly increased IL6 expression, which was not stated for explants derived from animals not treated with LPS [93]. Intracerebroventricular (icv) administration of LPS into the third ventricle increased the expression of IL6 in the ovine hypothalamic preoptic area during the reproductive season [94]. Further, IL1β injection into the third ventricular of the ovine brain caused a significant increase in IL6 and IL6ST expression in both photoperiods, while IL6R expression increased only during the short-day period at the level of the pineal gland [95].…”
Section: The Influence Of Leptin On Proinflammatory Cytokines During Inflammationmentioning
confidence: 99%
“…TNFR2, as the opposite of TNFR1, may promote tissue repair and angiogenesis [102]. In ewes in the follicular phase of the estrous cycle, it was stated that the ICV injection of LPS increased TNF expression in the preoptic area of the hypothalamus [94]. On the other hand, a study conducted on the ovine AP explants showed no effect of LPS on TNF expression [93].…”
Section: The Influence Of Leptin On Proinflammatory Cytokines During Inflammationmentioning
confidence: 99%
“…Studies on rats and sheep models indicated that both systemic LPS treatment and central administration of IL-1β, and TNFα into the region of the hypothalamus suppress the secretion of the gonadotropin-releasing hormone leading to downstream inhibition of the hypothalamic-pituitary-gonadal axis (HPG axis), the main neuroendocrine axis regulating reproduction [13,[16][17][18]. On the other hand, pharmacological inhibition of the synthesis of pro-inflammatory cytokines in the hypothalamus during endotoxin-induced immune challenge has been shown to reduce the inhibitory effect of inflammation on the activity of the HPG axis in sheep during the follicular phase [19].…”
Section: Introductionmentioning
confidence: 99%
“…Another factor influencing the HPG axis, whose secretion shows day/night fluctuations, is interleukin (IL)-1β [22]. Our previous studies showed that, acting at the level of hypothalamus, proinflammatory cytokines, particularly IL-1β, are potent negative regulators of GnRH secretion in ewes [58][59][60]. The study on rats showed that there are day/night changes in the hypothalamic IL-1β mRNA expression.…”
Section: Discussionmentioning
confidence: 99%